2022
DOI: 10.3389/fphar.2022.854430
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Targeted PEGylated Magnetoliposomes for Hyperthermia-Mediated Controlled Release of Doxorubicin

Abstract: Doxorubicin (DOX) is a chemotherapeutic agent commonly used for the treatment of solid tumors. However, the cardiotoxicity associated with its prolonged use prevents further adherence and therapeutic efficacy. By encapsulating DOX within a PEGylated liposome, Doxil® considerably decreased DOX cardiotoxicity. By using thermally sensitive lysolipids in its bilayer composition, ThermoDox® implemented a heat-induced controlled release of DOX. However, both ThermoDox® and Doxil® rely on their passive retention in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…[32] They can be used in hyperthermic cancer treatment in the presence of an EMF generating heat, which enables nanoparticles or LP lysis or heat-induced pore formation for drug release. [37,38] MLs can selectively target anticancer therapeutics to the tumor site, providing more successful cancer therapy and overcoming the limitations of conventional therapy. [33] MLs are challenging to maintain their stability due to their susceptibility to Fe 2+ -and Fe 3+ -induced membrane peroxidation, which can successfully be prevented by the antioxidant properties of QU.…”
Section: Introductionmentioning
confidence: 99%
“…[32] They can be used in hyperthermic cancer treatment in the presence of an EMF generating heat, which enables nanoparticles or LP lysis or heat-induced pore formation for drug release. [37,38] MLs can selectively target anticancer therapeutics to the tumor site, providing more successful cancer therapy and overcoming the limitations of conventional therapy. [33] MLs are challenging to maintain their stability due to their susceptibility to Fe 2+ -and Fe 3+ -induced membrane peroxidation, which can successfully be prevented by the antioxidant properties of QU.…”
Section: Introductionmentioning
confidence: 99%
“…FA-functionalization on nanobiomaterials often brings them enhanced cellular uptake in many cancer cells by facilitating the FA-receptor-mediated endocytosis process. 50,51 In this work, murine melanoma (B16F10) cell line was used to test the in vitro cell proliferation inhibition of FA-functionalized nanogels because it has been shown express high level of FA receptors, 52,53 Meanwhile, normal cell line CHO-K1 with a low-level expression of FA receptors, was used as the negative control. First, the cytotoxicity of P(MAA-PMA)-1 nanogels were evaluated with CHO-K1 and B16F10 cell lines by CCK-8 assay.…”
Section: Cell Proliferation Inhibition Of Surface Functionalized Nano...mentioning
confidence: 99%
“…To generate the necessary magnetic field to increase and control the temperature during the hyperthermia with nanoparticles, there are commercial heat inducers [43], such as the equipment DM 100 system, nB nanoscale Biomagnetics (Zaragoza, Spain) and Mag-neTherm (NanoTherics) (Warrington, United Kingdom) [44][45][46]. All these instruments provide an accurate control of temperature during hyperthermia in cellular cultures and in tumors generated in laboratory animals.…”
Section: Magnetic Hyperthermiamentioning
confidence: 99%
“…Using a target for cancer cell receptors in magnetoliposomes is a strategy that has been studied. Cintra et al (2022) reported that folate-target magnetoliposomes loaded with doxorubicin were more cytotoxic for folate receptor overexpression cells [46]. In recent years, the research on magnetoliposomes has increased (Table 2).…”
Section: Magnetoliposomesmentioning
confidence: 99%